A qualitative investigation of the barriers to help-seeking amongst members of the public presented with symptoms of new onset rheumatoid arthritis - Simons, Gwenda (J Rheumatol, 2015)
OBJECTIVE: Treating patients with rheumatoid arthritis (RA) within 3 months of symptom onset leads to significantly improved clinical outcomes. However, many people with RA symptoms wait for a long time before seeking medical attention. In order to develop effective health interventions encouraging people to seek help early, it is important to understand what the general public knows about RA, how they would react to the symptoms of RA and what might delay help-seeking. METHOD: Qualitative interviews were conducted with 38 members of the general public (32 females) without any form of inflammatory arthritis about their perceptions of RA symptoms and decisions to seek help were they to experience such symptoms. The interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. RESULTS: A number of barriers and drivers to help-seeking were identified, and grouped into five themes: perceived causes of symptoms; factors related to presentation, location and experience of symptoms; perceived impact of symptoms on daily life; self-management of symptoms; and General Practitioner related drivers and barriers. CONCLUSIONS: This study is the first to investigate barriers to and drivers of help-seeking in response to the onset of RA symptoms in individuals without a diagnosis of RA. It has revealed a number of additional factors (e.g. the importance of the location of the symptoms) besides those previously identified in retrospective studies of patients with RA. Together with the data from previous research, these findings will help inform future health interventions aimed at increasing knowledge of RA and encouraging help-seeking.